2021
DOI: 10.3389/fmicb.2020.615887
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Chimeric Endolysin, Lys109 With Enhanced Lytic Activity Against Staphylococcus aureus

Abstract: As the incidence of antibiotic-resistant bacteria has become increased, phage endolysins are believed as one of the promising alternatives to antibiotics. However, the discovery of potent endolysin is still challenging because it is labor intensive and difficult to obtain a soluble form with high lytic activity. In this respect, the modular structures of Gram-positive endolysins can provide an opportunity to develop novel endolysins by domain rearrangement. In this study, a random domain swapping library of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…Previous reports have shown that endolysin added from the outside results in cell death, which may be due to two reasons. One is that endolysin can directly attack the molecular structure of Gram-positive bacteria, which have no outer membrane [56,57]. The other is that endolysins with antibacterial effects in vitro are generally applied to bacteria together with outer membrane permeabilizers [58][59][60], as Gram-negative bacteria have an outer membrane, preventing antibacterial effects [54].…”
Section: Purified X2-lys Shows Antibacterial Activitymentioning
confidence: 99%
“…Previous reports have shown that endolysin added from the outside results in cell death, which may be due to two reasons. One is that endolysin can directly attack the molecular structure of Gram-positive bacteria, which have no outer membrane [56,57]. The other is that endolysins with antibacterial effects in vitro are generally applied to bacteria together with outer membrane permeabilizers [58][59][60], as Gram-negative bacteria have an outer membrane, preventing antibacterial effects [54].…”
Section: Purified X2-lys Shows Antibacterial Activitymentioning
confidence: 99%
“…PGHs have become extensively studied for 20 years, e.g., [ 11 , 15 , 17 , 53 , 54 , 59 , 61 , 63 , 64 , 65 , 67 , 69 , 82 , 106 , 141 , 142 , 143 , 144 , 148 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 ,…”
Section: Phage-encoded Peptidoglycan Hydrolases (Pghs)mentioning
confidence: 99%
“…Examples of pathogens against which they have been developed include Bacillus anthracis [ 180 ], Clostridium spp. [ 178 , 244 ], Enterococcus faecium [ 183 ], P. aeruginosa [ 205 ], S. aureus [ 186 ], S. epidermidis [ 188 , 245 ], S. pneumoniae [ 185 ], K. pneumoniae [ 184 ], and many others [ 27 ]. They can be used to treat biofilms [ 164 , 188 , 205 , 246 , 247 , 248 , 249 , 250 ], can be applied to mucosal surfaces [ 251 ], and are active against persister cells [ 188 , 252 , 253 ].…”
Section: Phage-encoded Peptidoglycan Hydrolases (Pghs)mentioning
confidence: 99%
“…Crystal violet staining was used to examine the biofilm-inhibitory activity of the lysin, which reduced S. aureus CCARM 3090 and S. aureus RN4220 biofilms by 3-fold compared to its parental lysin SA012. At a concentration of 1000 nM Lys109 reduced the OD570 of the S. aureus CCARM 3090 and S. aureus RN4220 biofilms from 1 (control) to <0.2 in both cases ( Son et al, 2021 ). CF-301 has also demonstrated impressive anti-biofilm activity in vitro .…”
Section: Phage Lysinsmentioning
confidence: 99%